The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11368-014-0960-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure alteration of a sandy-clay soil by biochar amendments

Abstract: Purpose The aim of the present study was to investigate structure alterations of a sandy-clay soil upon addition of different amounts of biochar (f bc ). Materials and methods All the f bc samples were analyzed by high energy moisture characteristic (HEMC) technique and 1 H nuclear magnetic resonance (NMR) relaxometry. HEMC was applied in order to evaluate aggregate stability of biocharamended soil samples. 1 H NMR relaxometry experiments were conducted for the evaluation of the pore distributions through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(64 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…Biochar particles often have lower density than soil particles (Blanco‐Canqui, 2017). Biochar can also decrease soil bulk density and increase porosity by improving soil aggregation (Baiamonte et al, 2015). Pyrolysis at increasing temperatures increases the internal porosity (i.e., micropore space) of the biochar.…”
Section: Biochar and Soil Erodibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Biochar particles often have lower density than soil particles (Blanco‐Canqui, 2017). Biochar can also decrease soil bulk density and increase porosity by improving soil aggregation (Baiamonte et al, 2015). Pyrolysis at increasing temperatures increases the internal porosity (i.e., micropore space) of the biochar.…”
Section: Biochar and Soil Erodibilitymentioning
confidence: 99%
“…Studies have found that biochar application can increase wet aggregate stability by 3 to 226% (Blanco‐Canqui, 2017). The high variability in biochar effectiveness on increasing aggregate stability can be attributed to differences in soil texture and biochar particle size (Baiamonte et al, 2015; Blanco‐Canqui, 2017). Addition of fine biochar can enhance aggregation more in sandy soils than in silty clay and clayey soils.…”
Section: Biochar and Soil Erodibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These effects of biochar application, however, depend on various factors such as the soil types, the type of feedstocks used for charring, pyrolysis conditions and the amount of biochar applied to the soils (Abel et al 2013;Glaser et al 2002; Barnes et al 2014). In this context, Baiamonte et al (2015) found that the incorporation of biochar into the sandy-clay soil increased soil aggregate stability by improving the porosity, the field capacity, and the maximum available water.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the high-energy moisture characteristic (HEMC) technique and the powerful 1 H nuclear magnetic resonance (NMR) relaxometry to evaluate changes in aggregate stability and pore size distribution of biochar-amended soils, Baiamonte et al (2014) showed that aggregate stability improved as a biochar was progressively added to a sandy-clay soil. Since the recognition of the interaction mechanisms between water and biochar is of paramount importance to understand why biochar soil amendments improve soil fertility and crop production, a more detailed analysis of the 1 H NMR relaxation was performed.…”
mentioning
confidence: 99%